Trichosanthes cucumerina as a promising non-toxic antimalarial agent against Plasmodium berghei NK65 in animal model - Baba, Mohd Shukri; Abdul Jalil, Muhamad Aiman (2019)
As the most threatening human parasitic disease, the malarial etiological agents were reported to be resistant against nearly all current antimalarial drugs. This study demonstrated how the manipulation of natural planted vegetable, Trichosanthes cucumerina promisingly can solve a manifestation of this disease in animal model. The four days suppression test (4DST) in Plasmodium berghei NK65-infected male mice (25-30 g, 6-8 weeks old) showed that 82.5 % of the inhibition rate by T. cucumerina-dH20 extract at 10 mg/kg body weight (bw) and 50 % of the treated mice had survived for more than 9 months post-infection. Besides, there was a positive relationship between the mice survival and the ability to inhibit the parasites growth. The results for biochemical tests were significantly situated in the normal ranged and histologically, no abnormalities found on the selected vital organs. This study evidenced that T. cucumerina has a promising antimalarial activity and could be manipulated for the welfare of both animal and human, as well as for environmental sustainability.